Status Leukosit dan differential Leukosit Tikus Putih (Rattus norvegicus L.) Periode Laktasi Setelah Diberi Suplement Telur Puyuh Organik - Hasan Basri (Universitas Islam Negeri Mataram, 2018)
The purpose of this research is to know the status of the Leukocyte differential leukocyte and rats (Rattus norvegicus L.) lactation period after the grant of a supplement to the quail eggs are organic. This research is a type of experimental research with Random Design complete using 4 treatments and 5 replicates. The data obtained were analyzed with Anova, if there is a real difference continued test Duncan at 95% confidence level (α = 0.05). Analysis with the software SPSS 16.0 for windows. T0: Control Treatment; T1: (Rattus norvegicus L.) lactation period were given supplements of the eggs produced by quail fed commercial feed; T2: (Rattus norvegicus L.) lactation period were given supplements of the eggs produced by a given organic feed quail standard; T3: (Rattus norvegicus L.) lactation period were given supplements of the eggs produced by quail fed organic feed. Based on the number of leukocytes results showed different results real (P < 0.05), the number of neutrophils, basophils, esonofil shows a different result is not real (P > 0.05), whereas the number of lymphocytes showed different results real (P < 0.05). Supplementation of organic quail eggs could be maintain the condition Leukocyte status in the lactation period of (Rattus norvegicus L.).